Identification of a novel α-glucosidase inhibitor from Melastoma dodecandrum Lour. fruits and its effect on regulating postprandial blood glucose. (15th January 2023) - Xu, Yang; Rashwan, Ahmed K.; Ge, Zhiwei; Li, Yuting; Ge, Hengju; Li, Jiaxin; Xie, Jiahong; Liu, Shiyu; Fang, Jie; Cheng, Kejun; Chen, Wei
Highlights: Chemical constituents of Melastoma dodecandrum Lour. (MDL) fruit were identified. Anthocyanins and proanthocyanidin derivatives were discovered for the first time in MDL. A novel α-glucosidase inhibitor was identified as casuarictin. Casuarictin bound α-glucosidase competitively, occupying the catalytic site. Abstract: Melastoma dodecandrum Lour. (MDL) extracts have shown potent α-glucosidase inhibitory activity, suggesting MDL might be a good source of α-glucosidase inhibitors. The aim of the study was to identify compounds in MDL extracts with α-glucosidase inhibitory activities and evaluate their effect on postprandial blood glucose as well as elucidating the underlying mechanisms of inhibition. A total of 34 polyphenols were identified in MDL fruits, among which 10 anthocyanins and three proanthocyanidin derivatives were discovered for the first time. Dosing mice with MDL extracts (100 mg/kg body weight, by gavage) was associated with a significantly decrease in postprandial blood glucose concentrations after oral administration of maltose. The most potent α-glucosidase inhibitor was identified as casuarictin (IC50 of 0.21 μg/mL). Casuarictin bound competitively to α-glucosidase, occupying not only the catalytic site but also forming strong hydrogen bonds with α-glucosidase residues. Therefore, casuarictin derived from MDL fruits might be used as novel α-glucosidase inhibitor in functional foods or other dietary products.